Evaluasi Pelaksanaan Pembangunan Proyek Dengan Menggunakan Metode Earnede Value - Reski Meliya, Kiki; Purnama Sari, Dewi; Arrie Rafshanjani, Muhammad (Jurnal Etnik: Ekonomi-Teknik, 2022)
The Earned Value method is one of the tools used in project management which refers to cost and time. The existence of project indicators in terms of cost and time allows prevention so that the implementation of a project goes according to plan. Earned value method, it is necessary to evaluate at a time to determine the performance of a project. Housing for the poor which is carried out by the Aceh Barat district government aims for the convenience of the community, not all people are able to build comfortable and healthy homes because, for example, when their husband dies, their income is limited. This research examines the implementation of housing projects for the poor. The implementation of this project has been in accordance with the contract that has been scheduled with a completion time of 180 days (6 months). The population in this study is by measuring the cost and time in the implementation of the construction work of the Dhuafa Housing Rehabilitation, Johan Pahlwan District, West Aceh Regency. The method used in this research is a field study with the sample in this study using a survey of images taken when going down the field. This research aims to study and determine the performance in the implementation of the earned value method in project implementation using special allocation funds, and to determine whether the implementation is going according to the predetermined plan or not.